Utilizing Comic Strips for Learning Adjective - Dina Kartikawati (STKIP PGRI Tulungagung, 2024)
English as one of international language is really important in current life. That is the reason why English given to students. Not only high school students but also it is given to elementary students. First year of high school students are deemed necessary to master of class of words or part of speech to know the meaning and the function of words in English structure. One word can be categorized in more than one different function. For example “book” it can be categorized as noun which means “buku” and verb wich mean “memesan”. Ing English, a noun can be converted into adjective by adding affixes. Students consider that it is difficult to convert them. They need to memorize the words. In this study, the writer wants to describe the comic strips used in learning process in classroom. The writer wants to describe how teacher use comic strips as a media to teach adjective in classroom. The population of this study is the first grade students of one of Junior High School in Tulungagung. By utilizing the comic strips, students seemed more interested and more enthusiastic in learning.